A study of pattern of maxillofacial fractures and its complications - Mittal, Seema; Dall, Tejinder Sing; Kapoor, Sudershan; Mittal, Raman (International Surgery Journal, 2020)
Background: Incidence of maxillofacial fractures is quite high worldwide. A very important aesthetic function is served by maxillofacial skeleton moreover the prominent position of maxillofacial skeleton makes it more susceptible to fracture. Methods: A prospective study was done to assess the main etiology and pattern of maxillofacial fractures of 60 patients who came to the emergency department of Sri Guru Ram Das Institute of Medical sciences and Research between January 2018 and June 2019. Results: Total number of patients taken for this study were 60. The number of male patients were 56 (93.33%) and number of female patients were 4 (6.66%) and male to female ratio was (14:1). The age range spanned from 11 years to 70 years with (mean age=37.30 years, SD=14.27). Primary etiologic factor for maxillofacial fractures was road traffic accidents (49, 81.66%), followed by fall (8, 13.33%), and assault accounted for (3, 5%). Total 229 fractures were present in 60 patients. Concerning the anatomical site of fractures, it was explored that most common site of fractures is orbit (59, 25.72%) followed by fractures of maxilla (55, 24%) and zygomatic complex (35, 15.28%). Infection was most common complication and was present in 2 (3.33%) of the patients during hospital stay. 21 (35%) of the patients had associated head injury and maximum patients 49 (81.66%) were treated by open reduction and internal fixation. Conclusions: It is concluded, that main etiology of maxillofacial trauma is road side accidents. Therefore, strict compliance of traffic rules can avoid such injuries.